Inhibition of human cytochromes P450 in vitro by ritonavir and cobicistat - Hossain, Md. Amin; Mikus, Gerd (Journal of pharmacy and pharmacology, 2017)
Objectives: Ritonavir and cobicistat are strong inhibitors of human cytochrome P450-3A (CYP3A) isoforms, and are used clinically as pharmacokinetic boosting agents for other antiretroviral drugs. Data reported by the manufacturer suggest that cobicistat is a more selective inhibitor of CYP3A than ritonavir. However, this claim has not been validated in clinical studies. This study evaluated the in-vitro inhibitory potency of ritonavir and cobicistat vs a series of human CYP isoforms. Method: The model system utilized human liver microsomes and isoform-selective index substrates. Key findings: Ritonavir and cobicistat both were strong inhibitors of CYP3A4, with IC50 values of 0.014 and 0.032 μm, respectively. A component of inhibition was time-dependent (mechanism-based). Neither drug meaningfully inhibited CYP1A2 (IC50 > 150 μm). CYP2B6, CYP2C9, CYP2C19 and CYP2D6 were inhibited by both drugs, but with IC50 values exceeding 6 μm. Conclusions: Consistent with previous reports, both ritonavir and cobicistat were highly potent inhibitors of CYP3A. Both drugs were weaker inhibitors of other human CYPs, with IC50 values at least two orders of magnitude higher. There was no evidence of a meaningful difference in selectivity between the two drugs.